Peroxisome Proliferator-Activated Receptor-γ-Mediated Polarization of Macrophages in Leishmania Infection - Marion M. Chan; Nagasuresh Adapala; Cui Chen (PPAR Research)
Infection is the outcome of a contest between a pathogen and its host. In the disease leishmaniasis, the causative protozoan parasites are harbored inside the macrophages. Leishmania species adapt strategies to make the infection chronic, keeping a balance between their own and the host's defense so as to establish an environment that is favorable for survival and propagation. Activation of peroxisome proliferator-activated receptor (PPAR) is one of the tactics used. This ligand-activated nuclear factor curbs inflammation to protect the host from excessive injuries by setting a limit to its destructive force. In this paper, we report the interaction of host PPARs and the pathogen for visceral leishmaniasis, Leishmania donovani, in vivo and in vitro. PPAR expression is induced by parasitic infection. Leishmanial activation of PPARγ promotes survival, whereas blockade of PPARγ facilitates removal of the parasite. Thus, Leishmania parasites harness PPARγ to increase infectivity.